Poikiloderma of Civatte: a review. (August 2012) - Katoulis, Alexander C; Rigopoulos, Dimitrios; Tzima, Korina; Stavrianeas, Nikolaos G
Poikiloderma of Civatte (PC) is a common acquired poikiloderma of the face and neck. It runs a chronic, benign course, producing only cosmetic disfigurement. PC most often affects middle-aged individuals of lighter skin phototypes, especially perimenopausal females. The etiopathogenesis appears to be multifactorial. Genetic factors, cumulative sun exposure, low estrogen levels of the menopause and contact sensitization, mainly to perfumes, have all been implicated. PC presents with pink to brownish reticular patches symmetrically distributed over the V, the sides of the neck and the upper chest, invariably sparing the anatomically shaded areas. Based on the predominating clinical feature, PC has been classified into erythemato-telangiectatic, pigmented and mixed type. The histologic picture is characteristic, but not pathognomonic. Solar elastosis of the upper dermis is the sine qua non feature. Differential diagnosis should include congenital and acquired poikilodermas and other causes of reticulate pigmentation of the neck. Lasers are the mainstay in the treatment of PC, especially the pulsed dye laser. Good results have also been reported with intense pulsed light sources. Strict photoprotection and avoidance of perfumes are the main preventive measures.